Thoracic involvement in IgG4-related disease in a UK-based patient cohort - Corcoran, J; Culver, E; Anstey, R; Talwar, A; Manganis, C; Cargill, T; Hallifax, R; Psallidas, I; Rahman, N; Barnes, E (Elsevier, 2017)
IgG4-related disease (IgG4-RD) is a multi-system fibro-inflammatory disorder with classical histopathological findings, often in the context of elevated serum IgG4 levels. The thoracic manifestations of IgG4-RD are numerous and can mimic several common and better known conditions. The objective of this study was to outline the frequency and nature of thoracic involvement in a prospective cohort of IgG4-RD patients who met defined diagnostic criteria. Over 40% of IgG4-RD patients had clinicoradiological and/or histological evidence of thoracic involvement, predominantly mediastinal lymphadenopathy, the majority associated with multi-system disease outside the chest. Thoracic involvement was associated with a higher serum IgG4 level, potentially representing greater disease activity or spread. Our data highlight the diverse nature of thoracic IgG4-RD, and the importance of knowledge and recognition of the condition among respiratory physicians who are likely to encounter this disease entity on an increasing basis.